Hungary : Report on the Observance of Standards and Codes-Data Modules; An Update, April 2003. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This report presents update on the Observance of Standards and Codes-Data and Fiscal Transparency Modules for Hungary. Hungary continues to observe the Special Data Dissemination Standards' specifications for the coverage, periodicity, and timeliness of all data categories, including the detailed template on international reserves and foreign currency liquidity, and for the dissemination of advance release calendars. The metadata and summary methodologies underlying the economic statistics are also being regularly updated on the Dissemination Standards Bulletin Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet